Patient response and recurrence rate following adjunctive ascorbic acid to surgical gingival depigmentation technique: A case report with one year follow up - Hashem, Eman O.; Ezzatt, Ola M.; Fathi, Rehab F.; Abd-El-Gaber, Hala K. (Journal of Case Reports in Dental Medicine, 2025)
Objective: Ascorbic acid has an inhibitory effect on tyrosinase enzyme which is the key enzyme in melanogenesis. This case reported the effect of two application techniques of ascorbic acid following surgical gingival depigmentation on the recurrence rate of pigments. Methods: Â A 24-year-old healthy non-smoker girl was seeking non-expensive cosmetic treatment for unesthetic dark appearance of her gums for the last 5 years, but the possible recurrence of those pigments was her main concern. On examination, diffuse brown hyperpigmented patches was observed in the maxillary and mandibular anterior attached gingiva and diagnosed as physiological gingival moderate pigmentation with score 2. The surgical scalpel scraping procedure using number 15 blade was performed to remove all visible pigments followed by intra mucosal field injection of 1ml ascorbic acid using insulin syringe weekly for 1 month, then monthly for 5 months in maxillary labial gingiva. While, ascorbic acid gel was applied topically twice weekly for 6 months on mandibular labial gingiva in split mouth design. The long-term effect of the two application techniques was followed for one year. Results: No pigment recurrence was observed at 6 months but mild pigmentations were seen at 12 months for both techniques. The patient was more compliant to topical than injectable vitamin C treatment protocol, however she reported perception of slight recurring pigment after one year with topical vitamin C. Conclusion: Both adjunctive intramucosal injected or topical vitamin C were effective in delaying recurrence following surgical depigmentation up to 1 year.